Effect of a High-Fat Diet and Metformin on Placental mTOR Signaling in Mice - Grace, Matthew R.; Dotters-Katz, Sarah K.; Zhou, Chunxiao; Manuck, Tracy; Boggess, Kim; Bae-Jump, Victoria (American Journal of Perinatology Reports, 2019)
Objective This study was aimed to measure the effects of a high-fat diet and metformin on placental mechanistic target of rapamycin (mTOR) signaling in mice.Study Design Pregnant friend virus B (FVB)-strain mice were allocated on embryonic day (e) 0.5 to one of four groups; group 1: control diet (CD, 10% fat) + control treatment (CT), group 2: CD + metformin treatment (MT), group 3: high-fat diet (HFD, 60% fat) + CT, and group 4: HFD + MT. Metformin (2.5 mg/mL) was provided in water; CT mice received water. Fetuses and placentas were collected. Western blot measured placental p-Akt and p-S6 expression.Results 20 dams (five/group) and 192 fetuses were studied. Compared with CD-fed, HFD-fed dams had higher placental p-Akt protein expression (p < 0.0001). Among HFD-dams, placental p-Akt was higher in metformin-treated compared with control-treated (p < 0.001). Among CD-fed dams, there was no significant difference in placental p-S6 expression in MT versus CT groups. Among HFD-fed dams placental p-S6 expression was lower in those exposed to metformin-treated versus controls (p = 0.001).Conclusion Increased placental mTOR signaling and metformin inhibition of placental mTOR signaling only occurred in the presence of an HFD exposure. These findings suggest that metformin may modulate placental mTOR signaling in the presence of metabolic exposures during pregnancy.
Keywords: metformin; mTOR; mice; high-fat diet